THE MAIN FEATURES OF LIGHT INDUSTRY IN THE ECONOMY OF UZBEKISTAN - Mahmudov Baxriddin Jurayevich (International Engineering Journal For Research & Development, 2021)
This article examines the theoretical aspects of the factors that further increase the effectiveness of marketing activities of light industry enterprises, a leading industry in Uzbekistan, the experience of developed countries, the process of forming assortment policy, their resource market activities and pricing strategies.